PROGRAM COACHING CLINIC DALAM MENINGKATKAN KUALITAS PEMAIN MUDA BULU TANGKIS DI DESA AIK MUAL - Burhan, Zakir; Herlina, Herlina; Ripai, Agus Sari M. (Devote: Jurnal Pengabdian Masyarakat Global, 2024)
Badminton is a type of game that requires good speed and agility. Improving playing skills can affect the quality of the game, especially for badminton players. In addition, improving the playing skills of the community in general is also very important. Therefore, the Lecturer of Physical Education at the Education Institute of Nusantara Global held a Coaching Clinic for the community to expand and increase knowledge and quality of play. This study aims to evaluate the effectiveness of two agility training methods, footwork and shadow, this training can improve the performance of PBSI badminton players. Training methods included lectures, demonstrations, question and answer sessions, and direct practice. Results indicated a significant improvement in participants' fundamental badminton knowledge after the training sessions. Footwork training proved to be more effective in improving agility than shadow training. Further development of this training program is recommended to increase effectiveness and long-term impact, by utilizing technology and local community cooperation to achieve a healthier and more successful community in badminton.